2021
DOI: 10.3390/plants10061148
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Characteristics, Peel Nutritional Compositions, and Their Relationships with Mango Peel Pectin Quality

Abstract: Mango peel, a byproduct from the mango processing industry, is a potential source of food-grade mango peel pectin (MPP). Nonetheless, the influence of fruit physical characteristics and phytochemicals of peels on their correspondent pectin level has never been examined, particularly when high-quality food additives are of commercial need. Subsequently, the ultimate aim of the present study was to comprehend their relationship using chemometric data analyses as part of raw material sourcing criteria. Principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 105 publications
1
22
0
2
Order By: Relevance
“…The coffee pulp was then dehydrated by sun-drying for 2 weeks followed by hot air drying until constant moisture content was reached (4.0–6.0%). The dried material was ground to a fine powder using a high-speed food processor for subsequent uses [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coffee pulp was then dehydrated by sun-drying for 2 weeks followed by hot air drying until constant moisture content was reached (4.0–6.0%). The dried material was ground to a fine powder using a high-speed food processor for subsequent uses [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Coffee pulp powder was analysed for proximate compositions according to the methods of the Association of Official Analytical Chemists (AOAC, 2000) [ 62 ]. Crude fibre content was analysed using the fibre analyser (Fibertherm FT12, Gerharadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a higher fruit ripeness leads to a greater content of pectin from fruit peel [40]. Wongkaew et al [6] reported that the physical properties of fruit physical properties (Colour, D a , D g , R a , sphericity, surface area and percentage yield of fruit parts) can be used to distinguish mango varieties.…”
Section: Mango Varietymentioning
confidence: 99%
“…Lactic acid production [75] Single cell protein production [76] Sugar source [77] Sources for functional ingredients Pectin [6,10,12,13] Phenolic compounds [78][79][80] Carotenoid [16,71] Functional food ingredient • Noodles, bread, biscuits, sponge cakes, other bakery products and yogurt [81,82] Dietary fibre…”
Section: Biotechnological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation